modernization Of The Budgetary System In Algeria - Berkennou, Salih; Abdat, Abdelouahab (جامعة الوادي University of Eloued, 2025)
This research paper aims to examine the reform of the budgetary system by exploring the shift from a consumption-based logic to an approach centered on the optimal exploitation of financial resources and windfall revenues, particularly from oil. The study highlights the reforms imposed by economic necessity, within the context of a centrally planned system in the post-independence era, the transition to a market economy in the early 1990s, and the period of booming oil revenues at the start of the 2000s. Based on a comprehensive analysis of Algeria’s public finance indicators and key macroeconomic variables, and through an examination of the major components of budgetary reform as defined by Organic Law No. 18-15 on Finance Laws, this study concludes that the revival of the Algerian economy is closely dependent on the implementation of results-oriented development programs and the reinforcement of the domestic economic fabric. To this end, the establishment of a coherent medium- and long-term fiscal strategy is essential; not only for effective performance management but also for ensuring the sustainability of both financial and macroeconomic indicators. Such a strategic orientation is fundamental to achieving long-term economic balance and resilience.
Modernization of the Budgetary System in Algeria: Transition from a Logic of Consumption to a Logic of Exploitation" - Analytical Study -
مقال
Keywords: key economic metrics; budgetary balance; budgetary reform; results-based management